Granularity of corporate debt - Jaewon Choi; Dirk Hackbarth; Josef Zechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We study to what extent firms spread out their debt maturity dates across time, which we call granularity of corporate debt. We consider the role of debt granularity using a simple model in which a firm's inability to roll over expiring debt causes inefficiencies, such as costly asset sales or underinvestment. Since multiple small asset sales are less costly than a single large one, firms may diversify debt rollovers across maturity dates. We construct granularity measures using data on corporate bond issuers for the 1991-2011 period and establish a number of novel findings. First, there is substantial variation in granularity in that many firms have either very concentrated or highly dispersed maturity structures. Second, our model's predictions are consistent with observed variation in granularity. Corporate debt maturities are more dispersed for larger and more mature firms, for firms with better investment opportunities, with higher leverage ratios, and with lower levels of current cash flows. We also show that during the recent financial crisis especially firms with valuable investment opportunities implemented more dispersed maturity structures. Finally, granularity plays an important role for bond issuances, because we document that newly issued corporate bond maturities complement pre-existing bond maturity profiles.
urn:nbn:de:hebis:30:3-325039
Keywords: G13; G31; G32; G33; 330; Capital Structure; Debt Structure; Debt Maturity